Influence of Time-Dependent Power Dissipations on the Ageing Behavior of Thick-Film Resistors - G. de Mey; E. Boone; G. De Tollenare (Active and Passive Electronic Components)
Reliability experiments on hybrid circuits are usually carried out by accelerated ageing test. The circuits or the components under test are stored at an elevated ambient temperature and the change of their electric properties is controlled at regular times. The situation becomes entirely different if the temperature rise is due to the power dissipation in the component under test and not caused by external means. In electronic circuits, power dissipations are expressed by a mean value, whereas the actual situation is generally a time-dependent function. The temperature will then also be time dependent. Therefore, ageing tests on thick film resistors will be presented in this contribution. Resistors are submitted to a DC power source and a pulse shaped one. Different ageing characteristics are observed.